New horizons in systemic sclerosis treatment: advances and emerging therapies in 2025 - Francesco Del Galdo; Cristiana Sieiro Santos (RMD Open)
Systemic sclerosis (SSc) is a rare, multisystem autoimmune disease characterised by vasculopathy, immune dysregulation, and progressive fibrosis, leading to significant morbidity and mortality. While recent EULAR recommendations have updated the standard of care for SSc, the field is rapidly evolving with novel therapeutic strategies and precision medicine approaches.Traditional immunosuppressive therapies—including mycophenolate mofetil, cyclophosphamide and rituximab—remain essential for controlling skin and lung involvement while autologous haematopoietic stem cell transplantation offers a proven disease-modifying option for selected high-risk patients. Tocilizumab and nintedanib have established roles in lung preservation in SSc-associated interstitial lung disease (SSc-ILD). In pulmonary arterial hypertension (PAH), early combination therapy with endothelin receptor antagonists and phosphodiesterase-5 inhibitors, complemented by newer agents such as selexipag and riociguat, has improved survival and quality of life. Advances in gastrointestinal, renal and musculoskeletal management continue to evolve, with promising roles for intravenous immunoglobulin and novel prokinetics.Crucially, emerging therapies—including CD19-targeted CAR-T cells, bispecific antibodies and agents targeting interferon pathways, BAFF, melanocortin, FcRn and PDE4B—reflect a shift towards personalised and biomarker-driven approaches. These innovations offer the potential to alter disease trajectory and support early, targeted intervention in SSc.This review provides an up-to-date synthesis of both current organ-based treatment strategies in major organ domains—skin, ILD, PAH, scleroderma renal crisis, raynaud’s phenomenon and digital ulcers, gastrointestinal and musculoskeletal involvement—and emerging therapies in SSc, with an emphasis on disease-modifying approaches and future directions in personalised care.